Investigation of the Impact of Uneven Fiber Distribution on Mechanical Properties of Composites Based on Voxel Models - Zhykhariev, Vladyslav; Misiura, Serhii; Vodka, Oleksii; Shapovalova, Mariia (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This study presents the results of numerical and experimental investigations into the impact of uneven fiber distribution in fiber-reinforced composites. A voxel-based model was developed using a Gaussian distribution with deviations of 5%, 10%, and 15% from an ideal hexagonal structure. Numerical simulations assessed the effect of microstructural statistical deviations on the elastic properties of composites. Computer vision methods were applied to analyze micrographs of real samples, enabling a comparison between modeled and actual material structures. The results demonstrated a significant influence of fiber misalignment on local stress concentrations and mechanical properties, validated by quantitative image analysis. This approach enhances the accuracy of predicting composite behavior under varying microstructural conditions.